Analisa Prediksi Tingkat Pengangguran dengan Jaringan Syaraf Tiruan - Prisa Marga Kusumantara; I Gede Susrama (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Up to now, unemployment is one of unresolved problems despite all efforts carried out to lower thenumber and always an interesting topic to discuss. This research tried to develop a prediction system to depictunemployment growth year by year using artificial neural network with backpropagation training.Backpropagation was used because of its capability to recognize trained data pattern and was suitable to beused in prediction system with a lot of data input.This application was developed using Visual Basic 6 and aimedto give prediction on unemployment growth to determine the number of workfields should be provided.Keywords: Artificial Neural Network, Unemployment, Backpropagation, Prediction